The Effect of Explant Type and Growth Regulators on Callus Induction in Passiflora quadrangularis - Paula OROS; Maria CANTOR; Corina CĂTANĂ (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture)
The initiation of callus culture and the stabilization of cell suspensions are important steps in obtaining a callus mass for in vitro secondary metabolite production. The protocol described here could be used for efficient callus induction in a wide range of Passiflora spp. Murashige and Skoog medium supplemented with 2,4-Dichlorophenoxyacetic acid (2,4-D) and Picloram (PIC) in different concentrations and combinations with Benzylaminopurine (BAP) and Kinetin (KIN) were used for culture initiation. A total of 11 treatments and different plant organs as explant source were tested. Callus proliferation was performed in solid and liquid culture systems. The interaction of factors showed that internodal segments callused at 100% on medium containing 2 mg/l 2,4-D and 0.5 mg/l BAP. On this culture medium, the leaf fragments also performed the highest callusing rate (98.33%). For P. quadrangularis, the liquid culture system proved to be superior in terms of cell mass and dry matter content, which can be explained by the better access to nutrients and water in a liquid medium. This research demonstrates that P. quadrangularis callus culture is strongly influenced by the plant growth regulators combination, the type of explants and culture system. The cell suspension obtained is the first step in the secondary metabolite production system.